2021
DOI: 10.3390/foods10061300
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Isothiocyanate-Protein Conjugates in a Vegetable-Enriched Bread

Abstract: Vegetables of the plant order Brassicales are believed to have health-promoting properties, as they provide high contents of glucosinolates (GLS) and deriving from these, enzymatically and heat-induced breakdown products, such as isothiocyanates (ITC). Besides their positive physiological effects, ITC are electrophilic and can undergo reactions with food components such as proteins. Following the trend of improving traditional food products with GLS-rich ingredients, interactions of ITC with proteins can dimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The formation of TUs in food by GLS-derived ITCs was reported previously. In these studies, formation of protein adducts after reaction of ITCs with lysine side chains in various foods such as curd with sprouts or vegetable-enriched bread was described (Krell, Cvancar, Poloczek, Hanschen, & Rohn, 2021;Kühn, von Oesen, Hanschen, & Rohn, 2018). Further, also arginine side chains of proteins form TUs with ITCs (Kawakishi & Kaneko, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of TUs in food by GLS-derived ITCs was reported previously. In these studies, formation of protein adducts after reaction of ITCs with lysine side chains in various foods such as curd with sprouts or vegetable-enriched bread was described (Krell, Cvancar, Poloczek, Hanschen, & Rohn, 2021;Kühn, von Oesen, Hanschen, & Rohn, 2018). Further, also arginine side chains of proteins form TUs with ITCs (Kawakishi & Kaneko, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that BITC treatment reduced the lipid components in the conidia and hyphae of A. ochraceus and that BITC could covalently bind to aminophospholipids and phosphatidylethanolamine in the cell membrane ( Clemente et al, 2016 ; Nakamura et al, 2019 ). In addition, ITCs can react with nucleophiles such as thiol groups in proteins ( Krell et al, 2021 ). The mechanism of BITC damage to cell membranes may be involved in a reaction with lipid components and proteins on the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Pronase E digestion was performed according to Kühn et al (2018) and Krell et al (2021) [ 55 , 56 ]. A total of 2 mL of a PBS buffer (pH 7.4) was added to the lyophilizates of the 0.5 mL supernatants (c.f.…”
Section: Methodsmentioning
confidence: 99%